Characterisation of cucumber mosaic virus (CMV) in Catharanthus roseus (L.)G. don and its effects on anticancer metabolite production - Mat, Mazidah (2012)
Natural virus-like disease symptoms such as mosaic and deformation of the leaves and flowers of malformed shape or slight colour-breaking of the petals were observed on Catharanthus roseus plants in Serdang, Selangor, Malaysia. Double antibody sandwich-enzyme linked immunosorbent assay (DAS-ELISA) detected cucumber mosaic virus (CMV) in high concentrations in the leaf extract of naturally-infected C. roseus as well as in the leaf extract of inoculated C. roseus. The purified virions were isometric particles with mean diameter 28.60 ± 0.48 nm and contained a central core. The virus induced systemic leaf mosaic on N. tabacum cv. White Burley, C. sativus, N. benthamiana and N. glutinosa. Local lesions and brown necrotic local lesions were produced on the inoculated leaves of C. amaranticolor and V.sesquipedalis, respectively. A 1000 bp DNA fragment covering the entire coat protein (CP) region of the purified virus was amplified using the primers CMVF1(5’-TAGACAT/ACTGTGACGCGA-3’) and CMVR2 (5’-GTAAGCTGGATGGACAAC-3’). The sequence obtained (GenBank accession number EU726631) revealed a 100% nucleotide and amino acid identities to a CP gene of CMV isolated from C. roseus in India (GenBank accession number EU310928) which is a member of subgroup 1B. Cytopathological study showed that CMV infection disrupted the chloroplast ultrastructure in the C. roseus leaf cells. The presence of large starch grains in the surrounding necrotic zones caused disintegration of the stromatic lamellae and grana, changing the chloroplasts symmetry. Complex membranous structures in the cells vacuoles and phytoferritin macromolecules in the chloroplast stroma were also observed in the leaf cells of CMV-infected C. roseus. Chloroplast was also the most altered organelle following CMV infection in the leaf cells of N. tabacum cv. White Burley, C. sativus and C. amaranticolor. A comparative HPLC analysis on the yields of two anticancer metabolites, vincristine and vinblastine in the C. roseus leaf,stem and root tissues at different growing stages indicated that CMV infection modified the metabolism of the metabolites. Following CMV infection, the peak production period of vincristine and vinblastine in leaves was delayed from four months old uninfected C. roseus plants to six months old CMV-infected plants. CMV infection also delayed the peak production period of vincristine in roots from five months old uninfected plants to seven months old infected ones. As for vinblastine, the peak production period was delayed from five months old uninfected plants to eight months old infected plants. Another remarkable alteration after CMV infection is that significant increases in the contents of vincristine in the infected root tissues, particularly at six to nine months old. The concentration of vinblastine which increased about two, four and seven-folds in the roots of six, seven and eight months old CMV-infected plants, respectively, could be another interesting finding of CMV modification, particularly in these anticancer compounds biosynthesis pathway in C. roseus plants.